2000
DOI: 10.1007/pl00000738
|View full text |Cite
|
Sign up to set email alerts
|

Decreased pulmonary levels of the anti-inflammatory Clara cell 16 kDa protein after induction of airway inflammation in asthmatics

Abstract: The Clara cell 16 kDa protein (CC16) maps to an atopy-associated region of chromosome 11 and has been ascribed an anti-inflammatory function. Using reverse-phase HPLC and Western blot analysis, we have evaluated the polypeptide pattern in bronchoalveolar lavage (BAL) fluid retrieved from asthmatics, before and after induction of airway inflammation by low-dose allergen inhalation challenge. A prominent decrease of CC16 was seen after induction of inflammation, and a further CC16 decrease was observed in lavage… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
27
1

Year Published

2002
2002
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(29 citation statements)
references
References 23 publications
(25 reference statements)
1
27
1
Order By: Relevance
“…Furthermore, our subjects were treated with only low to moderate doses of ICS, which also could explain why no inhibiting effect was seen on the increase in CC16 plasma levels. In a previous study, repeated low dose allergen challenge over seven consecutive days led to decreased concentrations of CC16 in BAL of subjects with allergic asthma (Lensmar et al 2000). In our study, CC16 levels in BAL were increased in single responders only, while the dual responders had significantly higher levels already at baseline.…”
Section: Discussionsupporting
confidence: 48%
See 1 more Smart Citation
“…Furthermore, our subjects were treated with only low to moderate doses of ICS, which also could explain why no inhibiting effect was seen on the increase in CC16 plasma levels. In a previous study, repeated low dose allergen challenge over seven consecutive days led to decreased concentrations of CC16 in BAL of subjects with allergic asthma (Lensmar et al 2000). In our study, CC16 levels in BAL were increased in single responders only, while the dual responders had significantly higher levels already at baseline.…”
Section: Discussionsupporting
confidence: 48%
“…In our study, CC16 levels in BAL were increased in single responders only, while the dual responders had significantly higher levels already at baseline. The allergen exposure in our study was higher and the time of sampling was different compared to the study by Lensmar et al (Lensmar et al 2000), with our results reflecting more of an acute inflammatory response. The absence of an increase in CC16 levels in BAL among the dual responders could be due to some form of desensitization of their club cells, thus reducing the anti-inflammatory response and the capacity of released CC16 to inhibit the LAR.…”
Section: Discussioncontrasting
confidence: 42%
“…SINGH and KATYAL [34] suggested that CC10 may function as a regulator of inflammation in the lung, a notion which is still a matter of debate [28,[52][53][54][55]. CC10 was reported to be decreased in various conditions of inflammation [53,56,57], and deficiency in CC10 as a result of transgenic experiments or in humans with a chronic CC10 deficiency, e.g. in long-term cigarette smokers [58,59], appears to be characterised by a tendency towards an exaggerated inflammatory response [53,55], and may contribute to carcinogenesis [59].…”
Section: Discussionmentioning
confidence: 99%
“…Impaired repair mechanisms in the human epithelium of the airway have also been demonstrated by the up-regulation of metalloproteinase-9 in extracellular matrix in arsenic-exposed subjects (36). Clara cell 16 protein, which is known to play an important role in protecting the alveolar epithelium of the lung in chronic inflammation (37,38), has also been impacted by arsenic exposure (27).…”
Section: Discussionmentioning
confidence: 99%